Clinico-Epidemiological Analysis and Treatment Outcomes of Snake Bite Cases: A Hospital-Based Study - Satish Nibedan; Bhawana S.; Srinivasa Reddy P.; Devendra Prasad K.J. (Indian Journal of Forensic Medicine and Pathology, 2026)
Context: Snake bite is a significant health hazard in tropical regions, particularly affecting rural populations engaged in agriculture. Objectives: To evaluate the demographic profile, clinical features, and outcomes of snake bite victims treated at a tertiary care hospital in southern India. Methods: This cross-sectional study analysed medical records of 51 snake bite cases admitted from September 2023 to November 2024. Data collected included age, gender, residence type, bite location, clinical features, complications, antivenom use, and patient outcomes. Statistical Analysis: Data were summarized using descriptive statistical measures including counts, proportions, mean values, and minimum–maximum distribution Results: Mean age was 35.2 years with 67% male predominance. Eighty percent were from rural areas. Pain (98%) and swelling (84.31%) were the main symptoms. Antivenom was given to 68.62% of patients. The mortality rate was 5.88%, with 94.11% patients surviving. Conclusion: Early hospital access, prompt antivenom administration, and supportive care significantly reduce snake bite mortality. Strengthening rural healthcare systems and community awareness are essential for better outcomes. Key Message: Timely hospital care with prompt antivenom administration and supportive treatment markedly improves survival and reduces mortality in snake bite cases, especially among rural populations.